Identification and functional characterization of circular RNAs in pericytes. (25th November 2020) - Glaser, S; Heumueller, A.W; Klangwart, M; Wiederer, A; John, D; Zeiher, A.M; Zehendner, C.M; Dimmeler, S
Abstract: Background: Circular RNAs (circRNAs) are generated by back-splicing. They are known to be robustly expressed in a variety of mammalian cell types and organism and have been reported to influence cell biology by acting e.g. as microRNA sponges or regulating host gene expression. Recently, our group reported functionally relevant circRNA expression in endothelial cells. Despite their important role in the cardiovascular system, the expression and function of circRNAs in pericytes is not well studied. Pericytes are perivascular mural cells, important for vessel maturation and endothelial barrier function. Their recruitment towards endothelial cells is mainly meditated by platelet-derived growth factor (PDGF) signaling. However, a more precise understanding of the regulation of pericyte differentiation and survival is necessary. Objective: Here, we analyse circRNA expression in pericytes and demonstrate biological relevance of the hypoxia regulated circular RNA PLOD2 (cPLOD2). Methods and results: Using RNA Sequencing in ribosomal depleted RNA we characterized the expression of circRNAs in human pericytes under normoxic and hypoxic (1% O2, 48h) conditions. We identified several circular RNAs being regulated upon hypoxia. The identified circular RNAs demonstrated resistance towards RNase-R digestion and lacking of poly-adenylation. Some of them were found to be localized and in the cytosol, whereas others also occur in the nucleus of the cells. Especially cPLOD2 raised our attention since it is significantly upregulated and robustly expressed upon hypoxia. Silencing cPLOD2 by siRNA resulted in significant de-differentiation of pericytes that went along with a loss of cell viability. Mechanistically, transcription factor screening assays revealed that silencing of cPLOD2 enhances the activity of the transcription factors ELK1/SRF, which have been documented to result in de-differentiation of smooth muscle cells. Conclusion: Here we characterize the expression pattern of circRNAs in human primary pericytes. Among others, cPLOD2 significantly regulates pericyte function. Our results indicate hypoxia as a major regulator of circRNA expression in pericytes and show that circRNAs are capable of regulating pericyte function by modulating activity of transcription factors. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Deutsche Forschungsgesellschaft (DFG) - SFB834; Deutsche Gesellschaft für Herz-Kreislaufforschung (DZHK)